The status of Barangay Reading Centers in Meycauayan, Bulacan fourteen years after the enactment of Republic Act 7743 - Sarmiento, Augustus Ruben C. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
The purpose of this study was to determine the status of Barangay Reading Centers (BRCs) in the 26 barangays of Meycauayan City, in the Province of Bulacan, 14 years after the enactment of Republic Act 7743 (RA 7743), otherwise known as An Act Providing for the establishment of Congressional City and Municipal Libraries and Barangay Reading Centers throughout the Philippines. It has been declared in the said act that it is a national policy to promote the moral and intellectual well-being of the people, elevate the literacy level of every Filipino and recognize the vital role of knowledge and information in nation-building by establishing these facilities. It is the function of such facilities a) to make available materials of wide array including those that are prescribed by DECS and national newspapers, and, d) to be used as a venue for activities aimed at increasing the literacy level of the members of its community.